Хомоцистеинот и неговата корелација со микроваскуларните и макроваскуларните компликации кај пациенти со дијабетес мелитус тип 2 - Богоева Костовска, Ксенија (Медицински факултет, УКИМ, Скопје, 2016)
Homocysteine (HCY) is a sulphur containing amino acid. The entire amount of homocysteine in the body is formed through the cycle of methylation of the amino acid methionine, as the primary and only source of homocysteine. Homocysteine is not found in the protein intake of the human food because of which there is no DNA code for it. The plasma free HCY is only 1%, while 70% is bound to albumin. The metabolism of HCY involves three enzymes: methionine synthase(MS) methylenetetrahydrofolate reductase (MTHFR), cystathionine B synthase (CBS) and the vitamins B6, B12 and folic acid as cofactors of these enzymes. In case of metabolic disturbance of the metabolism of HCY due to enzymatic defect or because of lack of intracellular cofactor, homocysteine accumulates in the cells, after which it is excreted from the cells and its plasma levels rise. The pathogenic mechanism and the role of homocysteine in the blood vessel damage is not yet clear, but high levels of homocysteine are allocated among the risk factors that lead to impairment of the endothelium of blood vessels accompanied by thrombosis and atherosclerosis. Data obtained from the studies researching the genesis and mechanisam of atherosclerosis are indicating that main process is based on molecular level where homocysteinemia in medium of oxidative stress and prolongated hyperglycemia can be potential factor in endothelial damage of the arterial blood vescels. Studies have indicated the presence of hiperhomocisteinemia, i.e. increased levels of homocysteine, in patients with diabetes mellitus type 2, with prevalence for a higher risk of cardiovascular disease, microvascular and macrovascular complications, as well as the occurrence of neuropathy in patients with elevated homocysteine. In support of these statements, goes an increased homocysteine measured in patients diagnosed with hypertension and dyslipidemia, as well as in patients with present diabetic retinopathy. The purpose of this survey is to obtain data that would prove the correlation of plasma homocysteine regarding the etiology of the microvascular and macrovascular complications of diabetes and the possibility of its use as an early predictor in the diagnosis of vascular complications in patients with diabetes mellitus. To prove correlation between elevated values of HbA1c, glycaemic control and plasma homocisteine, and their role in progression of complication in patients with diabetes mellitus type2. Methods: This paper is a longitudinal-prospective study that was conducted at the Clinic for Endocrinology, Diabetes and Metabolic Diseases in Skopje. The study have included 80 patients with diabetes mellitus 2, confirmed diagnosis and treated with insulin and oral treatment. The groups of patients were recruited continuously over the period of 9 months. During this period, patients have visit the clinic for regular check-up - screening visit. Recruited patients were divided into two groups: 50 patients diagnosed with vascular complications and a group of 30 patients without associated complications, which is mentioned as a control group. The results are processed using methods of descriptive and analytical statistics. Results: The study has included 80 patients with diabetes mellitus 2. From the preliminary results of the microvascular complications the most frequent and statistically significant is the prevalence of the nephropathy with 32%. Retinopathy was represented with 29% and microalbuminuria was detected in 27,5% of the patients. Among the macrovascular complications 31% of the patients were diagnosed with arterial hypertension and 12,50% with peripheral arterial diseases. In the present study higher levels of homocysteine within 16,05 μmol/l were detected in group of diabetic subjects with microvascular and macrovascular complications comparing to control group of patients where no complications were diagnosed and levels of homocysteine were among reference ranges, 10,44 μmol/l. In conclusion, it can be stated that it is expected that hiperhomocisteinemia represents a risk factor in the etiology of chronic complications in patients with diabetes mellitus type 2. However, further research would provide clear evidence of the impact of increased levels of homocysteine and its role in damage to the endothelium of blood vessels and the emergence of long-term vascular complications.
Докторска дисертација одбранета во 2016 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Чедомир Димитровски.
Keywords: homocysteine, endothelium, vascular complications, diabetes mellitus